Nationalism and Ethnicity: Images of the Ecuadorian Indians and the Imagemakers at the turn of the nineteenth century - Muratorio, Blanca (1993)
This essay will examine the explicit and the unspoken yet unhidden images of Ecuadoran Indians represented in those documents and at the Madrid exhibition. The dominant visual images of Ecuadoran Indians (mostly in engravings, drawings, and water colors) circulating among intellectuals, artists, and other powerful producers of public images at the turn of the century, undoubtedly contributed to the construction of the images apparent in the documents. They also seem to have influenced the selection and hierar- chization of the artifacts actually presented at the exhibition. I will argue that those narrative and visual images of the Indians became incorporated as important elements in the political rhetoric of an emerging nationalist ideology.